Acute Demyelination in a Person with Amphetamine Abuse. (18th October 2011) - Weis, Serge; Sachs, Hans; Büttner, Andreas
Abstract : We report the case of a 31-year-old woman, admitted to the hospital for chest pain, dying a few days later from septic multiorgan failure, and showing at autopsy foci of acute demyelination in the occipital lobe. Gas chromatography/mass spectrometry analysis revealed the presence of amphetamine in the demyelinated area, which might be considered as the pathogenic agent, since other causes for demyelination could be excluded. This case represents the first report showing a demyelinating process due to a street drug.